2018
DOI: 10.1097/opx.0000000000001164
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Lens Clearance Assessment with Biomicroscopy and Anterior Segment Optical Coherence Tomography

Abstract: Results from this study validate the ability of contact lens practitioners to observe and estimate the CCC in scleral lens fittings through the use of biomicroscopic viewing. Increasing experience with scleral lens fitting does not improve the correlation with measured CCC from digital or the AS-OCT. However, the intermediate and advanced groups display significantly less inter-observer variability compared with the novice group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…As the clinician gained more experience, it was possible to reduce the average difference between the subjective measures of CCC made with Slit Lamp and the objective measures recorded with ImageJ as well as to narrow the intervals of agreement. In addition, and according to Yeung and Sorbara [20], the overall standard deviation also decreased between V1m and V12 m, meaning that there was also a reduction in the variability of the differences. It is also observed on Figs.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…As the clinician gained more experience, it was possible to reduce the average difference between the subjective measures of CCC made with Slit Lamp and the objective measures recorded with ImageJ as well as to narrow the intervals of agreement. In addition, and according to Yeung and Sorbara [20], the overall standard deviation also decreased between V1m and V12 m, meaning that there was also a reduction in the variability of the differences. It is also observed on Figs.…”
Section: Discussionmentioning
confidence: 75%
“…One should think that this bias can be decreased as the fitter gains more experience, however there is some controversy about this. Yeung and Sorbara [20] concluded that, independently of the experience of the observers, there was an overestimation of clearance by an average of 103 μm when compared to AS-OCT measurement, with high correlations (r > 0.79).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On average, students significantly overestimated the extent of central corneal clearance, particularly for lower levels of corneal clearance (actual clearance about 100 μm, mean overestimation of 115 μm) than higher levels of corneal clearance (actual clearance about 340 μm, mean overestimation of 60 μm). Similarly, Yeung and Sorbara observed a mean subjective overestimation of about 100 μm for central corneal clearance (with sodium fluorescein) based on assessments of in vitro digital slitlamp images compared to OCT imaging across a range of apical clearance values (from 50 to 400 μm) and various levels of scleral lens fitting experience.…”
Section: Assessing the Fit Of Scleral Contact Lensesmentioning
confidence: 88%